2011
DOI: 10.1161/circimaging.110.962761
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Left and Right Atrial Remodeling With Atrial Fibrillation Recurrence After Pulmonary Vein Catheter Ablation in Patients With Paroxysmal Atrial Fibrillation

Abstract: Background-Left atrial (LA) remodeling is a factor in atrial fibrillation (AF) recurrence after pulmonary vein catheter ablation (CA), but right atrium (RA) remodeling has not been investigated for possible associations to AF recurrence. Methods and Results-Using 64-slice multidetector computed tomography, RA and LA volumes were measured 3-dimensionally before CA in 65 patients with initially proven idiopathic paroxysmal AF (mean age, 60Ϯ10 years, 81.5% men). The CA procedure was guided by CARTO Merge atrial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 34 publications
2
49
2
Order By: Relevance
“…The univariate and multivariate analyses found that LA diameter and a PM for AVB were associated with recurrence of AF. This finding also supports the results of previous studies [23][24][25] showing that the LA size is a well-known predictor of recurrence of AF after catheter ablation. Several mechanisms may account for the relationship between a PM for AVB and recurrence of AF.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The univariate and multivariate analyses found that LA diameter and a PM for AVB were associated with recurrence of AF. This finding also supports the results of previous studies [23][24][25] showing that the LA size is a well-known predictor of recurrence of AF after catheter ablation. Several mechanisms may account for the relationship between a PM for AVB and recurrence of AF.…”
Section: Discussionsupporting
confidence: 92%
“…20) RA remodeling is associated with AF recurrence. 25) Fourth, AVB may also contribute to recurrence of AF in the patients with a PM for AVB. Chronic AVB and the resulting slow idioventricular rhythm in a goat can lead to progressive atrial dilatation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the prolonged PR interval probably refl ects underlying atrial disease with atrial fi brosis or atrial dilatation. Atrial fi brosis [19][20][21] and atrial dilatation [22][23][24] are associated with increased recurrence of AF after catheter ablation. Second, a prolonged PR interval results in increased LA pressure, delayed and ineffective mitral valve closure, and diastolic mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…25) The LA size is a well-known predictor of recurrence after catheter ablation for AF. [22][23][24] In addition, mechanoelectric feedback 26) and proliferation of arrhythmogenic fibroblasts 27,28) secondary to increased LA pressure may also play a role in promoting recurrence of AF. Third, a prolonged PR interval is associated with endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%